Legalisasi Supremasi Eksekutif? Studi Sosio-Legal terhadap Reformasi Kementerian di Indonesia - Risky, Saiful; Ramadhan, Febriansyah; Esfandiari, Fitria (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2025)
This article will explore how the amendment to Law No. 39/2008 on State Ministries that removed the maximum limit on the number of ministries, has significant constitutional and political implications for Indonesia’s presidential system. This study employs a socio-legal or interdisciplinary approach by analyzing the normative aspects of legislation alongside the political dynamics behind the policy revision. The findings indicate that the removal of ministerial limits is primarily driven by political accommodation rather than administrative efficiency. This increasingly expansive governance model risks creating a bloated bureaucracy that lacks effectiveness in executing governmental functions. The findings indicate that without a limit on the number of ministries, the institutional precedent is difficult to reverse due to mechanisms of path dependency, which reinforce resistance to bureaucratic reform. To address the risk of constitutional regression and the weakening of the principle of checks and balances, this article recommends policy reconstruction by revising the Law on State Ministries to explicitly set a maximum of 34 ministries, as well as a limited amendment to Article 17 of the 1945 Constitution of the Republic of Indonesia so that the restriction is constitutionally enshrined. In this way, the reform is expected to uphold constitutional supremacy, improve bureaucratic efficiency, and maintain institutional stability within the framework of good governance. Artikel ini akan mengeksplorasi perubahan Undang-Undang Nomor 39 Tahun 2008 tentang Kementerian Negara yang menghapus batas maksimal jumlah kementerian menimbulkan implikasi konstitusional dan politik yang signifikan dalam sistem pemerintahan presidensial Indonesia. Penelitian ini menggunakan pendekatan socio-legal atau interdisipliner antara ilmu hukum dan ilmu politik, dengan menganalisis aspek normatif dalam peraturan perundang-undangan serta dinamika politik di balik revisi kebijakan tersebut. Hasil penelitian menunjukkan bahwa penghapusan batas jumlah kementerian lebih didasarkan pada akomodasi kepentingan politik daripada pertimbangan efisiensi administrasi. Model tata kelola pemerintahan yang semakin ekspansif ini berisiko menciptakan birokrasi yang gemuk dan kurang efektif dalam menjalankan fungsi pemerintahan. Temuan menunjukkan bahwa tanpa pembatasan jumlah kementerian, 'preseden institusional' sulit dibalik akibat mekanisme 'path dependency', yang memperkuat resistensi terhadap reformasi birokrasi. Untuk mengatasi risiko 'constitutional regression' dan melemahnya prinsip 'checks and balances', artikel ini merekomendasikan rekonstruksi kebijakan melalui revisi UU Kementerian Negara yang menetapkan batas maksimal 34 kementerian secara eksplisit, serta amendemen terbatas Pasal 17 UUD NRI 1945 agar pembatasan bersifat konstitusional. Dengan demikian, reformasi ini diharapkan menegakkan supremasi konstitusi, meningkatkan efisiensi birokrasi, dan menjaga stabilitas kelembagaan dalam kerangka good governance.